The first man in Rome - McCullough, Colleen, 1937-2015. (New York : Avon Books, 2008)
McCullough's epic tale of ancient Rome explores the power struggle between an ambitious military man and a man who lost his fortune to pleasure.
Keywords: Marius, Gaius, -- approximately 157 B.C.-86 B.C. -- Fiction; Marius, Gaius, -- approximately 157 B.C.-86 B. C; 265 - 30 B.C.; Statesmen -- Rome -- Fiction; Statesmen; Rome -- History -- Republic, 265-30 B.C. -- Fiction; Rome (Empire); Fiction; Biographical fiction; Historical fiction